Enrollment Decision‐Making in U.S. Forestry and Related Natural Resource Degree Programs. Issue 1 (23rd August 2017) - Rouleau, Mark; Sharik, Terry L.; Whitens, Samantha; Wellstead, Adam
Abstract : Core Ideas: Typical forestry and related natural resources students are attracted to their program because it satisfies a need to be outdoors and with nature. Forestry and related natural resources students are hesitant to enroll in the program due to concerns about earning potential and the desire to avoid contentious political issues. Women are hesitant to enroll in a forestry and related natural resources program due to concerns about their gender, work locations, and work conditions. The environmental stewardship aspect of forestry and related natural resources programs may boost enrollment rates and address issues related to underrepresented minority enrollment. This article investigates enrollment decision‐making trends among students currently enrolled in forestry and related natural resource (FRNR) degree programs in the United States. We conducted an online survey administered to all student participants attending the Society of American Foresters (SAF) National Convention in Salt Lake City, UT, in 2014 to obtain our enrollment decision‐making data. Students were asked to rank the enrollment factors they considered most important to their decision to enroll, and factors that caused them to hesitate when enrolling in their degree program. We found that the "typical" FRNR enrollee was a person who enjoyed being outdoors and had an affinity toward nature, while being attracted to the idea of working outdoors on subject material that pertained to nature in general. We also found that there were many important differences between the "typical" FRNR enrollee and their minority counterparts. For example, women were found to be significantly more hesitant about enrolling in a FRNR program than males (the dominant demographic of FRNR students). In addition to these differences, we found critical differences between degree program and specialty that also crossed gender lines. We report the results of these findings and discuss the implications for future recruitment efforts geared toward both boosting FRNR enrollment overall as well as increasing FRNR student diversity.